Appolinaire Djikeng: Lessons from the ugly pig - Djikeng, Appolinaire (International Fund for Agricultural Development, 2015)
Geneticist Appolinaire Djikeng discusses the role that livestock diversity can play in helping small scale African farmers overcome risk and vulnerability.